Therapeutic Effect of Cognitive Ability Activities Of Daily Life In the Day Hospital Clients Grasia Schizophrenia in Yogyakarta - Suharsono Suharsono; Siti Arifah; Nuning Sri Wahyuni (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Schizophrenia refers to a group of severe, disabling psychiatric disorders marked by withdrawal from reality, illogical thinking, possible delusions and hallucinations, and other emotional, behavioral, or intellectual disturbances. These disturbances may affect everything from speech, affect, and perception to psychomotor behavior, interpersonal relationships, and sense of self. The outcome of this disorder can infulence of the ability of activity daily living. The aim of this study was to know the influence of cognitive therapy toward the ability of activity daily living in schizophrenic client at Grhasia hospital Yogyakarta province. Pra experiment design : one group Pre test post was applied. The sampel of this study consist o f 17 schizophrenic client and purpossive sampling was applied. Barthel index was used to measure the ability of activity daily living before and after cognitive therapy. The result of this study has shown that there was an increase of ability of activity daily living after cognitive therapy by Z : 3,537 and p value 0.00. The result of this study could guide the nurse to perform cognitive therapy in dealing with some problems in client with schizophrenia